7-3x=7+2(6-x)

Simple and best practice solution for 7-3x=7+2(6-x) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7-3x=7+2(6-x) equation:


Simplifying
7 + -3x = 7 + 2(6 + -1x)
7 + -3x = 7 + (6 * 2 + -1x * 2)
7 + -3x = 7 + (12 + -2x)

Combine like terms: 7 + 12 = 19
7 + -3x = 19 + -2x

Solving
7 + -3x = 19 + -2x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '2x' to each side of the equation.
7 + -3x + 2x = 19 + -2x + 2x

Combine like terms: -3x + 2x = -1x
7 + -1x = 19 + -2x + 2x

Combine like terms: -2x + 2x = 0
7 + -1x = 19 + 0
7 + -1x = 19

Add '-7' to each side of the equation.
7 + -7 + -1x = 19 + -7

Combine like terms: 7 + -7 = 0
0 + -1x = 19 + -7
-1x = 19 + -7

Combine like terms: 19 + -7 = 12
-1x = 12

Divide each side by '-1'.
x = -12

Simplifying
x = -12

See similar equations:

| -5(3-7n)=90 | | 8x-12+x=-4x-3 | | -11+-16= | | 2z-5=3z-4 | | -14+15=m-7 | | -6(x+1)=6-5x | | 36+36-18= | | ln(1-3x)+C=ln(x)+C | | 81x^2+18x+6=equation | | 7x+1=9x+(-17) | | 10-16x-6-5x=7 | | -15=-4m+5[5] | | .16(y-3)+.04=.14y-.03(30) | | x+(x*.20)+(x*.10)=5000 | | 12x+1=11x+3 | | 23-p=8 | | 6+5(-7+7v)=146 | | w^2+8w-9=0 | | x+(x-6)=116 | | 10+6=-2(7x-8) | | 85=5(1+4n) | | 12x+9-4x-4=7-x+30 | | 4x+37-6x=3-8x+4 | | 4(3x+7)=-17+21 | | 2(6n+1)=62 | | -8+3x-4=5x+10 | | 12x+4=11x+11 | | 6(3-z)*5=-z | | 9=4p+6-p | | 3x+3=8x+13 | | 200x-1400= | | 4(-3+1)=-8 |

Equations solver categories